Gender and educational background: Influence on entrepreneurial intention (EI) in economics learning - Jun Surjanti; Tony Seno Aji; Zainur Rahman; Heny Musfidah (Institute of Advanced Engineering and Science, 2019)
Student behavior is one of important aspects to determine both direction and process in the Economic Theory learning. This study aims to draw how those two factors, gender and educational background, support the emergence and development of student entrepreneurial intention. This study is a quantitative study using explanatory survey. Data were analyzed by two-way ANOVA design to find the relationship/influence of gender and educational background on student entrepreneurial intention. The population was 111 students. Saturated samples were used as sampling technique. The results indicate that both gender and educational background had no significant influence on student entrepreneurial intention. Therefore, lecturers can override both when preparing learning strategies and design for Economics Theory courses.